2016
DOI: 10.4293/jsls.2016.00007
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Total Mesorectal Excision With Single-Incision Laparoscopy for Rectal Cancer

Abstract: Background and Objectives:There has been great enthusiasm for the technique of transanal total mesorectal excision. Coupled with this procedure, we performed single-incision laparoscopic surgery for left colon mobilization. This is a description of our initial experience with the combined approach.Methods:Patients with distal or mid rectal cancer were included. The operation was performed by 2 teams: one team performed the single-incision mobilization of the left colon via the right lower quadrant ileostomy si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Patients reported minimal postoperative pain. Further studies on the long-term outcome are warranted (33). The first experience with this minimally invasive approach was demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Patients reported minimal postoperative pain. Further studies on the long-term outcome are warranted (33). The first experience with this minimally invasive approach was demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Cohort studies have shown the feasibility of this new technique and 1,2 improved total mesorectal excision (TME) specimen quality, potentially minimizing surgical morbidities. [9][10][11][12][13] GelPOINT Path Transanal Access Platform (Applied Medical, Rancho Santa Margarita, CA, USA) is currently the commonly-used adjunct because of its flexibility and air-sealing quality during transanal dissection. 7,8 of The TaTME technique has been applied in conjunction with various traditional procedures to achieve maximal benefits to patients.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 of The TaTME technique has been applied in conjunction with various traditional procedures to achieve maximal benefits to patients. [9][10][11][12][13] GelPOINT Path Transanal Access Platform (Applied Medical, Rancho Santa Margarita, CA, USA) is currently the commonly-used adjunct because of its flexibility and air-sealing quality during transanal dissection. However, it is difficult to establish stable imaging and results in extra costs to the health-care system because of the costly single-use consumables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Все авторы размещали порт для ЕЛД либо в умбиликальной области, когда не планировали превентивную илеостому, либо в правом мезогастрии на месте будущей стомы [21][22][23][24][25]. Во всех описанных случаях практиковали высокое лигирование нижних брыжеечных сосудов с D3лимфодиссекцией [21][22][23][24][25][26]. Страховой дренаж выводили либо через контрапертуру на передней брюшной стенке [25], либо параректально [24].…”
Section: Introductionunclassified